Jurnal Problematika Pembelajaran bahasa Arab Di STAIN Majene - Riki, Riki (Program Studi Bahasa dan Sastra Arab STAIN Majene, 2023)
This article aims to describe the problems of Arabic learning in STAIN Majene, both in terms of linguistics and non-linguistics. The problem in learning Arabic is a problem that has elements that can hinder the process of learning Arabic. Linguistic problems such as phonetics (sound system), mufrodat (vocabulary), morphology (shorof), syntax (nahwu) and semantics. And non-linguistic problems such as teachers / educators, students and media facilities and infrastructure. The problem of learning Arabic varies greatly according to the age of the student / student and the environment in which to study.